2022
DOI: 10.3390/ani12243461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genetic Variation of the Sorting Nexin 29 (SNX29) Gene on Growth Traits of Xiangdong Black Goat

Abstract: Previous studies have found that the copy number variation (CNV) and insertion/deletion (indels) located in the sorting nexin 29 (SNX29) gene, which is an important candidate gene related to meat production and quality, are associated with growth traits of African goats and Shaanbei white cashmere goats. However, the genetic effects of SNX29 genetic variation on growth traits of Xiangdong black (XDB) goat (a representative meat goat breed in China) are still unclear. The purpose of this study was to detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Among these, the IFT88 and CHRM2 genes are regarded as candidate genes for mohair fineness in Tibetan cashmere goats ( Bai et al, 2022 ), while the SDC1 gene is associated with coarse and fine skin tissues of Liaoning cashmere goats ( Nazari-Ghadikolaei et al, 2018 ). Similarly, the ITCH gene plays a potential role in regulating mohair and coat color traits in the Iranian Markhoz goat ( Wang et al, 2021 ), whereas the FGF12 gene is involved in the production of fleece in Inner Mongolia Cashmere goats ( Chen Y et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the IFT88 and CHRM2 genes are regarded as candidate genes for mohair fineness in Tibetan cashmere goats ( Bai et al, 2022 ), while the SDC1 gene is associated with coarse and fine skin tissues of Liaoning cashmere goats ( Nazari-Ghadikolaei et al, 2018 ). Similarly, the ITCH gene plays a potential role in regulating mohair and coat color traits in the Iranian Markhoz goat ( Wang et al, 2021 ), whereas the FGF12 gene is involved in the production of fleece in Inner Mongolia Cashmere goats ( Chen Y et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on complete genomic architecture, including population structure, genome diversity and evolutionary selective sweeps, in relation to this important genetic resource is scant. Earlier, studies relied on mapping of the mitochondrial genome ( Mao-Liang et al, 2016 ) and elucidating single-gene associations with growth traits ( Chen Y et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, six primer pairs were designed for amplification using the Primer-BLAST tool (https://www.ncbi.nlm.nih.gov/tools/primer-blast/; accessed on 1 August 2023). MC1R and GAPDH were used as reference genes [31]. The relevant primers are listed in Table S1.…”
Section: Primer Designmentioning
confidence: 99%
“…The total qPCR reaction system consisted of 10 µL, comprising 5 µL of 2 × SYBR Premix Ex Taq (Takara, Japan), 0.5 µL of DNA, 0.5 µL of each primer, and 3.5 µL of ddH 2 O. The reaction conditions and thermal profiles were as previously described by Chen et al [31]. Relative copy number (RCN) was calculated from the ∆∆Cq value using the following formula [32]:…”
Section: Copy Number Analysis Mrna Expression and Statistical Analysismentioning
confidence: 99%
“…A circRNA of the SNX29 gene regulated the proliferation and differentiation of muscle cells ( 9 ). Studies have shown that the SNX29 gene plays a key role in subcutaneous fat deposition in Xiangdong black (XDB) goats, and the SNX29 CNV is significantly associated with the chest and abdominal girth of XDB goats ( P < 0.01) ( 10 ). Based on the above, the SNX29 gene was selected to be studied in this study.…”
Section: Introductionmentioning
confidence: 99%